Mineralogy and geochemistry of ferromanganese oxide deposits from the Chukchi Sea in the Arctic Ocean - Yingchun Cui; Xin Liu; Chenguang Liu; Jingjing Gao; Xisheng Fang; Yanguang Liu; Weiguo Wang; Yuansheng Li (Arctic, Antarctic, and Alpine Research, 2020)
Abundant ferromanganese oxide deposits were recovered from the Chukchi Sea in the Arctic Ocean during the 7th Chinese Arctic Scientific Expedition in August 2016. Representative samples were collected to perform a mineralogical and geochemical analysis and elucidate their origin. Their mineral phases consist of todorokite, buserite, and birnessite, along with a small quantity of detrital minerals (quartz, feldspar, serpentine, kaolinite, and illite). Their elemental composition is rich in Ni and Mn compared to ferromanganese oxide deposits from other locations in the Chukchi Sea. The total rare earth element (REE) concentration varied from 138.95 to 207.23 μg/g with an average of 164.75 μg/g. The post-Archean Australian shale–normalized REE patterns have a slightly negative Ce anomaly and a positive Eu anomaly. The comprehensive geochemical and mineral data show that they have a mixed hydrothermal and diagenetic origin.